Tuberculosis infection in HIV vs. non‐HIV patients. Issue 8 (17th May 2021) - Rego de Figueiredo, I; Branco Ferrão, J; Dias, S; Vieira Alves, R; Drummond Borges, D; Torres, M; Guerreiro Castro, S; Lourenço, F; Antunes, AM; Gruner, H; Panarra, A
Abstract : Objectives: Tuberculosis (TB) is the most common opportunistic infection and cause of mortality among people living with HIV, and it is possible that it may also influence the evolution of the HIV infection. We assessed the differences between HIV‐positive and ‐negative people infected with TB. Methods: The present study is a cross‐sectional retrospective study by electronic record revision. We included patients admitted to a tertiary hospital with a diagnosis of TB between 2011 and 2016, comparing those with HIV coinfection with non‐HIV patients, according to demographic and clinical characteristics. Results: This study included 591 patients, of whom 32% were HIV‐coinfected. HIV‐TB patients were younger, with a predominance of male gender. Considering TB risk factors, there was a higher prevalence of homelessness and intravenous drug use in the HIV group. In the non‐HIV group, direct contact with other patients with TB and immunosuppression were more prevalent. Relative to TB characteristics, the HIV‐coinfected group presents with a higher prevalence of disseminated disease and a higher occurrence of previous TB infection. Cancer was the most frequent cause of immunosuppression in the HIV group and the number testing positive for TB via microbiological culture was lower. Assessment of microbiological resistance and in‐hospital mortality showed similar numbers in both groups. Conclusions: There are few papers comparing clinical course of TB between HIV‐infected and non‐infected patients. Our study differs from others in the literature as we focused on a country with middling incidence of TB and further characterized the differences between HIV‐infected and non‐infected patients which can contribute to the management of these patients.